TEKNIK PERSUASI BROSUR PROMOSI PENERIMAAN MAHASISWA BARU PERGURUAN TINGGI KEAGAMAAN BUDDHA DI INDONESIA - Suntoro, Suntoro (KREDO : Jurnal Ilmiah Bahasa dan Sastra, 2019)
The promotion of new student admission  of the Buddhist College is done in various ways, one of which is using brochures. Although this method has already been abandoned, for the Buddhist College, brochure still become the most favorite one. This study aims to find out persuasive techniques contained in the year of 2018-2019 academic brochure. The research method used was qualitative content analysis with the unit of analysis being ten academic brochures Buddhist College in Indonesia. Data collection techniques use documentation, while data analysis is done by matching methods with referential matching techniques and pragmatic techniques. The results of this study indicate that there are five persuasion techniques used in the academic brochure, namely rationalization, identification, suggestion, conformity, and compensation, while replacement techniques are not found in the brochure. Therefore, brochures should be designed creatively and attractively and have high persuasive values to attract more attention.